Calidad molinera, contenido de amilosa y proteína en cuatro líneas promisorias de arroz (Oryza sp.), cultivadas a una planta por sitio en Daule, Guayas - ROCAFUERTE GUAMANZARA, LADY LISSETH (2023)
The experimental work conducted in the Grain Quality Laboratory of the Faculty of Agricultural Sciences of the Technical University of Babahoyo, located at km 7.5 of the Babahoyo-Montalvo Road. The objectives were: to determine the milling quality of four promising lines of rice in samples from the Daule area; identify the amylose and protein content of four promising rice lines and select the best milling quality lines and to identify the best amylose and protein content lines. The study evaluated the quality of milling, amylose content using the promising rice lines PxJ-7, PxJ-17, PxJ-37 and PxJ-38, and the commercial variety SFL-11 was used as a control. Regarding the results, in relation to the variable percentage of shell the highest value corresponded to the promising line PxJ - 37, while, for the percentage of integral was the line PxJ - 7, the percentage of classified grains, the variety SFL-11 exceeded the lines studied. The variables rice (%), dust (%), protein content (%) were presented in a higher percentage in the line PxJ – 7. Regarding the white belly variable, the PxJ – 17 line exceeded the averages and the PxJ – 38 line had a higher amylose content (32.1 %). Line 38 and the commercial variety SFL11 had higher yields of classified grains and lower relative variability (%). The analysis of Conglomerates discriminated in Class I to the variety SFL 11 and grouped in Class II to the four promising lines.